Condutividade hidráulica efetiva e erodibilidade entressulcos de solos da bacia do Rio das Mortes - Bocuti, Edwaldo Dias (2016)
For the calibration and validation of water erosion prediction models in the areas of Cerrado is of fundamental importance the data acquisition in field. The objective of this study was to determine the effective hydraulic conductivity (Ke) and rill erodibility (Ki) and their correlation with physical and physical-hydric characteristics the soil. This work was developed in two chapters, the first entitled "Determining in field of effective hydraulic conductivity and interrill erobibilidade of soil Mato Grosso," and the second "Correlation of effective hydraulic conductivity and erodibility interrill with the physical attributes and physico-hidric the Cerrrado soil". This study was conducted in six areas called Pasto ponto 1 (PP1), Pasto Ponto 2 (PP2), Agrícola ponto 1 (Ap1), Agricola ponto 2 (Ap2), Cerrado1 (C1) and Sâo vicente1 (SV1), located in municipalities of Campo Verde and Santo Antônio do Leverger of Mato Grosso. For determination of Ki and Ke was used and a rain simulator. Correlation analyzes were initially performed with all six areas of study using the following soil properties: soil particle size, water clay dispersion, flocculation of clay, organic matter, total porosity, micro and macro porosity, evaluation index aggregate stability, bulk density and silt / clay ratio. The erodibility interrill are 2,44x105, 1,32x106, 1,56x105, 2,47x105, 8,56x104, 5,93x105 kg.s.m-4 to Ap1, Ap2, Pp1, Pp2, C1 and SVp1 respectively. The determined effective hydraulic conductivity are 81.52; 109.94; 30.63; 24.49; 48.31; and 28.37 mm h -1 for Pp1; Pp2; Ap1, Ap2, C1 and SV1, respectively. The rill erodibility was different (p≤0.05) between Ap2 and C1 areas. The hydraulic conductivity was different (p≤0.05) between Pp2 and Ap2 (p≤0.05). The attributes total sand, organic matter and percentage clay were significantly correlated with the independent effective hydraulic conductivity of the soil textural class of the study, showing that these attributes can be good predictors of effective hydraulic conductivity. For sandy soils attributes coarse sand, very fine sand and aggregate stability index present greater potential for predicting erodibility interrill. For clay soils attributes coarse sand, medium sand, average diameter, geometric mean diameter and aggregate stability index showed greater potential for predicting erodibility interrill.